2017
DOI: 10.1016/j.eucr.2017.03.016
|View full text |Cite
|
Sign up to set email alerts
|

High Grade Mucinous Urothelial Carcinoma of the Renal Collecting System: A Case Report

Abstract: High grade mucinous urothelial carcinoma is a rare pathological variant. There is still controversy as to its nomenclature and classification. We report the case of a 64 year old female with history of pelvic pain who was incidentally discovered to have a left upper pole renal mass. Left nephroureterectomy was performed and histopathological examination revealed high grade mucinous urothelial carcinoma. Accurate diagnosis of this distinct pathological entity will allow for better understanding of phenotypic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Ting et al reported a case report and literature review of bladder UC with abundant myxoid stroma in 2020 5 . Only two cases of mucinous UC which originated in the upper urinary tract were reported in 2014 and 2018 6,7 . The clinicopathological features of 19 cases including the present case are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Ting et al reported a case report and literature review of bladder UC with abundant myxoid stroma in 2020 5 . Only two cases of mucinous UC which originated in the upper urinary tract were reported in 2014 and 2018 6,7 . The clinicopathological features of 19 cases including the present case are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 72%
“…5 Only two cases of mucinous UC which originated in the upper urinary tract were reported in 2014 and 2018. 6,7 The clinicopathological features of 19 cases including the present case are summarized in Table 1. The population of mucin is quite different depends on cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations